Using artificial intelligence tools for translating computer terminology - Maryna Tymchyk; Timcsik Marina; Natalia Drabov; Драбов Наталія; Drabov Natália (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2025)
Abstract. The emergence of artificial intelligence (AI) technologies has significantly transformed the field of translation, streamlining processes through automation and enhancing both efficiency and accuracy. As the demand for precise translation of technical texts grows, particularly in rapidly evolving fields such as computer science, AI tools have become indispensable for professional translators. This article investigates various AI-powered solutions used in translating specialised computer terminology, focusing on different approaches to machine translation, including rule-based, statistical, and neural systems.The analysis examines the translation of selected English computer terms, lexico-syntactic units, and a fragment of a specialised computer vocabulary text into Ukrainian, comparing the performance of widely used systems such as Google Translate, DeepL, and ChatGPT. Our comparative study highlights the respective strengths and limitations of different machine translation tools, emphasising their ability(or inability) to preserve technical accuracy and context when handling complex or domain-specific vocabulary.The article also describes several popular AI-based computer-assisted translation (CAT) platforms, including Trados, Smartcat, Star Transit, and DéjàVu, and outlines their specialised features designed to support translators working with technical texts.The investigation demonstrates that despite significant advances in AI translation tools, expert human revision remains essential for achieving accurate and context-sensitive translations of computer-related texts. The article concludes by discussing current challenges and identifying open questions for further research, such as improving AI’s understanding of specialised terminology, enhancing its ability to capture linguistic nuances, and optimising workflows that integrate human expertise with AI efficiency to meet the demands of computer translation in the digital age.

Резюме. Поява технологій штучного інтелекту (ШІ) суттєво трансформувала сферу перекладу, спрощуючи процеси завдяки автоматизації та підвищуючи як ефективність, так і точність. Із зростанням потреби у точному перекладі технічних текстів, особливо в таких швидкозмінних галузях, як комп’ютерні науки, інструменти ШІ стали незамінними для професійних перекладачів. У статті досліджено різні підходи на основі ШІ, що використовуються для перекладу спеціалізованої комп’ютерної термінології. Акцентовано увагу на різноманітних напрямках машинного перекладу, зокрема статистичний, нейронний, машинний переклад на основі правил. Проведено аналіз перекладу вибраних англійських комп’ютерних термінів, лексико-синтаксичних одиниць та уривку тексту, що містить комп’ютерну термінологіюукраїнською мовою, із порівнянням ефективності широко використовуваних систем, таких як Google Translate, DeepL та ChatGPT. Наш порівняльний аналіз висвітлює відповідні сильні та слабкі сторони різних інструментів машинного перекладу, підкреслюючи їхню здатність (або неспроможність) зберігати технічну точність і контекст при роботі зі складною чи вузькоспеціалізованою лексикою. У статті описано декілька популярних платформ автоматизованого перекладу (CAT) на базі штучного інтелекту, зокрема Trados, Smartcat, Star Transit та Déjà Vu, а також окреслено спеціалізовані функції, призначені для підтримки перекладачів, які працюють із фаховими текстами. Результати дослідження демонструють, що, незважаючи на значний прогрес у розвитку інструментів машинного перекладу на основі ШІ, експертна перевірка перекладача залишається критично важливою для досягнення точних, контекстно-чутливих перекладів комп’ютерних текстів. У статті підсумовано сучасні виклики та визначено відкриті питання для подальших досліджень, такі якпокращення здатності ШІ розуміти спеціалізовану термінологію, підвищення його здатності передавати мовні нюанси та оптимізація робочих процесів, що поєднують досвід перекладачів із ефективністю ШІ для задоволення потреб комп’ютерного перекладу в цифрову епоху.

A mesterséges intelligencia (MI) technológiák megjelenése jelentős mértékben átalakította a fordítástudományt, automatizálással egyszerűsítve a fordítási folyamatokat, a hatékonyság és a pontosság növelése mellett. A technikai szövegek pontos fordítása iránti igény folyamatos növekedésével – különösen az olyan gyorsan fejlődő területeken, mint a számítástechnika – az MI-alapú eszközök nélkülözhetetlenné váltak a hivatásos fordítók számára. A tanulmány különféle mesterséges intelligencia által támogatott megoldásokat vizsgál, amelyeket a számítástechnikai szakszókincs fordítására használnak, különös tekintettel a gépi fordítás különböző megközelítéseire, beleértve a szabályalapú, statisztikai és neurális gépi fordítási rendszereket. Az elemzés az angol számítástechnikai terminusok, lexikai-szintaktikai egységek, valamint egy szakszókincsalapú szövegrész ukrán nyelvre történő fordítását vizsgálja, és összehasonlítja a széles körben használt eszközök (Google Translate, DeepL, ChatGPT) teljesítményét. Összehasonlító tanulmányunk rámutat az egyes gépi fordítóeszközök erősségeire és korlátaira, hangsúlyozva azok technikai pontosságának és kontextusmegőrző képességének meglétét vagy hiányát az összetett, szakterületi szókincs fordításakor. A kutatás továbbá bemutat több népszerű MI-alapú számítógépes fordítástámogató (CAT) rendszert is – köztük a Trados, Smartcat, Star Transit és Déjà Vu platformokat –, és ismerteti azokat a speciális funkciókat, amelyek a műszaki szövegekkel dolgozó fordítók munkáját támogatják. A vizsgálat azt is megállapítja, hogy az MI-fordítóeszközök jelentős fejlődése ellenére a szakértői fordítói lektorálás továbbra is elengedhetetlen a számítástechnikai szövegek pontos, kontextushű fordításához. A tanulmány a jelenleg fennálló kihívásokkal zárul, és olyan további kutatási kérdéseket fogalmaz meg, mint a mesterséges intelligencia szakszókincs-feldolgozásának fejlesztése, a nyelvi árnyalatok felismerésének javítása, valamint a humán szakértelmet és az MI-hatékonyságot ötvöző munkafolyamatok optimalizálása a digitális korszak fordítási igényeinek kielégítése érdekében.
Використання інструментів штучного інтелекту для перекладу комп’ютерної термінології
Mesterséges intelligencia alapú eszközök alkalmazása a számítástechnikai terminológia fordításában
Teljes kiadvány: https://aab-philologica.kmf.uz.ua/aabp/issue/view/9
Keywords: artificial intelligence; computer terminology translation; machine translation; statistical machine translation; neural machine translation; rule-based machine translation; CAT